An Agent-Based Approach for Strategic Alignment in Enterprise Systems: A Cancer Care Case - (:unkn) unknown (IEEE, 2018)
Enterprise systems are viewed as large-scale software systems, which are usually assembled through a number of protocols inspired by political coalitions. This is due to the fact that incompatibilities emerge through the nature of subsystems can only be avoided in a wider and comprehensive context, which can only come to existence in the corporate/strategic level of enterprises. Cancer care systems consist of a number of such individual systems that require alignment of principles and goals subjected to changes due to emerging circumstances in order to keep up with substantial efficiency, and a certain level of sustainability. In this position paper, an agent-based system is proposed comprising a set of autonomous and collaborating agents running a mathematical model to health-check the current status of the entire system and to produce maintenance and alignment operations to corresponding parts of the system. It helps align the strategical values and principles with the lower level operations infiltrating into the entire enterprise system. This prototypical idea can be extended for more configuration and maintenance.
Keywords: Cancer Care Informatics; Agent-based Computing; Strategic Alignment; Enterprise Systems